Riesgo de intentos autolíticos en adolescentes de la Comuna del Cantón Otavalo - Dávila Perugachi, Celeste Anahi (2024)
Non-suicidal autolytic attempts are considered self-inflicted actions that cause pain or superficial injuries; however, their objective is not intended to cause death. On the other hand, suicide implies a deliberate act of causing death. In the Tangali community, it has been observed a concerning rate of adolescents who have tried to commit suicide, which emphasizes the need to establish effective interventions. The present research aims to implement an educational plan addressed to the prevention of suicide attempts among the adolescents of the Tangali Community, located in the Otavalo cantón, a quantitative paradigm is used alongside a field, descriptive and action type of research, under an analytic-synthetic approach, historic-logic and systemic. Results: the affected adolescents are between 18-19 years old, thus representing 42% of the population in this research. Based on the SRQ-18 test, which was used as the instrument for this research, it was possible to identify prevalent symptoms of depression and psychological anxiety, such as chronic headaches (52%), feelings of nervousness, tension and boredom (62%), constant crying (68%) and difficulty for making decisions (60%), and frequent and easy fatigue (62%). In addition, 40% of the adolescents reported having had the perception of having consumed alcohol at least once. The proposed plan provides a whole approach that combines sanitary education with the promotion of mental health and preventive strategies, which also seeks to foster a community, supportive environment, thus promoting appropriate health development among young people, and in general among the inhabitants on the Tangali community.